Influence of Binary Ligands in Designing Cesium Lead Halide (CsPbX3, X = Cl, Br, I) Perovskite Nanocrystals-Oleic Acid and Oleylamine - Ananthakumar Soosaimanickam; Alejandro Saura; Noemi Farinós; Rafael Abargues (Nanoenergy Advances, 2023)
The surface chemistry of cesium lead halide perovskite nanocrystals has been elaborately studied in recent years and has proved the critical role of carboxylic acids and amines in the formation and stability of the nanocrystals. Specifically, a slight change in the concentration and ratio of the frequently used oleic acid and oleylamine critically influences the resultant phase and physical properties. Thus, understanding the delicate surface of cesium lead halide perovskite nanocrystals mainly relies on chemical bonding and the dynamic ligand environment of these two organic species. In this aspect, this review summarizes experimental findings about the critical role of oleic acid and oleylamine on the nucleation, growth, stability, phase, and morphology of cesium lead halide perovskite nanocrystals and their effect under different circumstances.